Structural assessment of the Chemical Engineering Administration Building at Universidad Central Applying the Ecuadorian Building Code (NEC15) - Siguenza-Flores, Alejandra (2026)
This research project focuses on the structural evaluation of the Administration Building of the Faculty of Chemical Engineering at the Central University of Ecuador, emphasizing its seismic vulnerability in accordance with the Ecuadorian Construction Standard (NEC). The building, in operation for 11 years, was built during a transitional regulatory period, making it essential to assess its behavior under severe seismic events. The methodology includes non-destructive tests such as the rebound hammer test (ASTM C-805) to determine concrete strength, and pachometry to locate steel reinforcement. Ambient vibration testing was used to determine the building’s actual fundamental period, which was compared with the results of a modal spectral analysis using structural modeling software. The model was calibrated by incorporating equivalent diagonals to represent the stiffness of existing masonry. Finally, a nonlinear static analysis (Pushover) was conducted using the capacity spectrum method (FEMA 440), enabling the development of the capacity curve and evaluation of structural performance levels. The findings provide insight into the current condition of the structure and offer valuable input for institutional decision-making regarding its continued use or potential retrofitting.